(untitled) - 1929-; Pfeffer, Wendy; Chernyshova, Anna (New York, NY, 2016)
Explains how sounds are made and the purposes they serve for both humans and other animals.-
Accelerated Reader AR
Keywords: Sound; Juvenile literature; Sound; Juvenile works